PERAN PEREMPUAN NELAYAN DALAM MEMBANTU EKONOMI KELUARGA DI KELURAHAN MALABERO - Sella, Tiara; Safitra, Linda (JURNAL ILMIAH IDEA, 2024)
This study aims to explore the role of women in supporting the household economy of fishing families in Kelurahan Malabero, Teluk Sagara Subdistrict, Bengkulu City. The research method used is a qualitative method with a phenomenological approach. The theoretical framework applied in analyzing the findings is George Herbert Mead’s Symbolic Interactionism Theory. Qualitative research is a procedure that generates descriptive data. The study involved eight informants. Data collection techniques included observation, interviews, and documentation. For data analysis, the technique used follows Miles and Huberman’s model, which consists of data reduction, data display, and conclusion drawing. The findings of this study reveal that women in Kelurahan Malabero play a significant role in supporting their household economy by starting small businesses. Their involvement is driven by the uncertainty of income earned by their husbands from fishing activities. This study aims to explore the role of women in supporting the household economy of fishing families in Kelurahan Malabero, Teluk Sagara Subdistrict, Bengkulu City. The research method used is a qualitative method with a phenomenological approach. The theoretical framework applied in analyzing the findings is George Herbert Mead’s Symbolic Interactionism Theory. Qualitative research is a procedure that generates descriptive data. The study involved eight informants. Data collection techniques included observation, interviews, and documentation. For data analysis, the technique used follows Miles and Huberman’s model, which consists of data reduction, data display, and conclusion drawing. The findings of this study reveal that women in Kelurahan Malabero play a significant role in supporting their household economy by starting small businesses. Their involvement is driven by the uncertainty of income earned by their husbands from fishing activities.